Composing the Will to Power: John Dewey on Democratic Rhetorical Education. Issue 4 (7th August 2016) - Crick, Nathan
Abstract : In order to highlight the genuinely radical nature of John Dewey's educational and democratic vision this essay articulates a vision of contemporary rhetorical education that is grounded in a pragmatic rereading of Friedrich Nietzsche's concept of the "will to power." Drawing from Dewey's treatment of the will to power in Human Nature and Conduct, I argue that rhetorical pedagogy seeks to arouse, channel, and finally compose the impulses of students through the activity of intelligence in such a way that reflects and advocates for students' interests within a democratic ethic of advocacy, criticism, and deliberation.